2017
DOI: 10.18632/oncotarget.15590
|View full text |Cite
|
Sign up to set email alerts
|

PRSS3 is a prognostic marker in invasive ductal carcinoma of the breast

Abstract: ObjectiveSerine protease 3 (PRSS3) is an isoform of trypsinogen, and plays an important role in the development of many malignancies. The objective of this study was to determine PRSS3 mRNA and protein expression levels in invasive ductal carcinoma of the breast and normal surrounding tissue samples.ResultsBoth PRSS3 mRNA and protein levels were significantly higher in invasive ductal carcinoma of the breast tissues than in normal or benign tissues (all P < 0.05). High PRSS3 protein levels were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…However, in bladder, lung, and esophageal cancers, tumor occurrence and development are promoted by downregulation or silencing of PRSS3 expression . Furthermore, PRSS3 expression level is an independent predictor of prognosis in some tumors . To clarify the expression levels of PRSS3 in GC tissues, we assessed its expression in a tissue microarray constructed from matched samples of 175 patients with GC after radical resection (D2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in bladder, lung, and esophageal cancers, tumor occurrence and development are promoted by downregulation or silencing of PRSS3 expression . Furthermore, PRSS3 expression level is an independent predictor of prognosis in some tumors . To clarify the expression levels of PRSS3 in GC tissues, we assessed its expression in a tissue microarray constructed from matched samples of 175 patients with GC after radical resection (D2).…”
Section: Discussionmentioning
confidence: 99%
“…17,18,24 Furthermore, PRSS3 expression level is an independent predictor of prognosis in some tumors. [13][14][15][16] To clarify the expression levels of PRSS3 in GC tissues, we assessed its expression in a tissue microarray constructed from matched samples of 175 patients with GC after radical resection (D2). The results suggest that the expression of PRSS3 is higher in tumors than in normal adjacent tissues (P < 0.05), correlating with clinicopathological features of some cancer metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, PRSS3 was identified to be downregulated in non-small cell lung cancer and hepatocellular carcinoma [6,7]. On the contrary, high PRSS3 was found in epithelial ovarian cancer and breast cancer [8,9], implying that PRSS3 functions in a cell-or disease-context-dependent manner. Likewise, we previously observed that PRSS3 was remarkably increased in PC and promoted PC growth and metastasis by activating ERK/VEGF pathway [10].…”
Section: Introductionmentioning
confidence: 99%